Analisis Fungsi Sintaksis Kata Apa dan Mana dalam Bahasa Indonesia - Sri Puji Astuti (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2017)
The characteristic of interrogative sentence, one of them is the presence of  a question word of apa, mengapa, siapa and others. Apa and mana and its derivative forms are also often found in declarative sentences. In this paper, it is explained that it can fulfill syntactic functions of apa and mana and its derivative forms contained in sentences either interrogative sentences or declarative sentences. The data collection in this research is in the form of basic technique of tapping.This stage ends with an orthographic transcription in the form of recording on the data card systematically. In the data analysis was used the method of distribution namely the method of data analysis in the form of connection between phenomena in its particular language. The techniques used in this research were substitution, expansion and delisi techniques. Based on the results of the research, it is found that apa and mana and its derivative forms can fulfill the functions of S, V, O, complement, and Adverb. Expansion with kah does not change the function in sentence.